2015
DOI: 10.1155/2015/648415
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Objective and Subjective Burden of Informal Caregivers in Multiple Sclerosis

Abstract: Background. Home care for patients with Multiple Sclerosis (MS) relies largely on informal caregivers (ICs). Methods. We assessed ICs objective burden (Resource Utilization in Dementia measuring informal care time (ICT)) and ICs subjective burden (Zarit Burden Inventory (ZBI)). Results. ICs (N = 99) were spouses (70%), mean age 52 years, assisting disabled patients with a mean EDSS (Expanded Disability Status Scale) of 5.5, with executive dysfunction (mean DEX (Dysexecutive questionnaire) of 25) and a duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 41 publications
5
31
1
9
Order By: Relevance
“…The Twelve‐Item Short Form Survey Instrument scores were consistent with those for caregivers of PWEs observed in prior research and for caregivers of patients with traumatic brain injury, multiple sclerosis, and Parkinson disease . ZBI scores were in the mild‐to‐moderate burden range, consistent with the range seen in those conditions .…”
Section: Discussionsupporting
confidence: 81%
“…The Twelve‐Item Short Form Survey Instrument scores were consistent with those for caregivers of PWEs observed in prior research and for caregivers of patients with traumatic brain injury, multiple sclerosis, and Parkinson disease . ZBI scores were in the mild‐to‐moderate burden range, consistent with the range seen in those conditions .…”
Section: Discussionsupporting
confidence: 81%
“…Bayen et al (2015) found that 54% of carers reported perceived burden and the scores were associated with the disability progression and limited cognitive function, which contrasts with the earlier findings of Akkuş and Akdemi (2011). Burden scores in MS were high from the onset of the condition which can be due to the unpredictable nature of the disease (Bayen et al, 2015). The ZBI scores reported by Bayen et al, (2015) varied greatly from other studies.…”
Section: Zarit Burden Interview (Zbi)contrasting
confidence: 92%
“…Burden scores in MS were high from the onset of the condition which can be due to the unpredictable nature of the disease (Bayen et al, 2015). The ZBI scores reported by Bayen et al, (2015) varied greatly from other studies. The authors suggest that differences might arise from different ways of application of the instrument (questionnaires or interviews) (Rivera-Navarro et al, 2009).…”
Section: Zarit Burden Interview (Zbi)mentioning
confidence: 86%
See 2 more Smart Citations